Energy management and temperature control for the thermoelectric therapy device - Khairul Nisa Hamdan,; Afida Ayob, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cryotherapy is one of most popular treatments for treating injuries using cold applications due to various advantages that have been accepted by medical professionals like safe to use and able to reduce pain and inflammation if the treatment is given according to medical specifications. The existing devices in the market such as cryo-cuff will become more efficient if it is capable to control important parameter like cooling temperature during the treatment. Therefore, a study of the therapeutic device control system using thermoelectric module was carried out. This system is based on microcontroller Arduino which makes it convenient for the users to control the gel temperature during the treatment. The aim of the study is to design a cooling therapy device using thermoelectric module for cryotherapy, to design a system that can control temperature and to develop a prototype that can control the desired temperature of gel using Arduino. This prototype uses thermoelectric-cooler (TEC) which will convert electric energy to temperature difference on both sides of the TEC. The PID controller is implemented in the coding of Arduino to obtain a constant gel temperature. In conclusion, the prototype is able to control the temperature reading consistently. In this study, when the temperature is set to 8°C by the Arduino, the result shows the average temperature reading is 8.668°C. Thus, it can be concluded that this thermoelectric therapy device can control the gel temperature set by the user.